การพัฒนาสูตรและกระบวนการผลิตข้าวพองเคลือบสารละลายไรซ์เบอร์รี่ - เขื่อนเพชร, กฤติยา; จันทร์ศรีบุตร, ณัชชา; ลิขิตสิทธิกุล, ภัสชญา (Thai Journal of Science and Technology, 2019)
Abstract The objective of this research was to formulate and develop process of crispy rice coated with riceberry solution. Four coating solution formulas were studied including mulberry juice mixed with coconut oil (MC), riceberry bran solution mixed with coconut oil (RC), mulberry juice mixed with butter (MB) and riceberry bran solution mixed with butter (RB). It was found that moisture content, water activity (aw) and hardness values of all solutions coated crispy rices were in the range of 7.64-7.91 %wb, 0.40-0.45 and 22.45-31.86 kgforce, respectively. The RB formula coated crispy rice got the highest sensorial score of liking color (p < 0.05). The overall acceptability score was slightly like, there was no significant difference from those of other coating formulas (p ³ 0.05) and had the lowest cost. Three ratios of coating solution to crispy rice (0.5 : 1, 0.75 : 1 and 1 : 1) were investigated. The result showed that the coating solution and crispy rice at the ratio of 0.75:1 was suitable due to providing a smooth surface covering and got the highest sensorial score of overall acceptability (p < 0.05) in moderately like level. The optimum drying condition was 70 °C for 3 hours. The healthy coating formula solution was developed. Riceberry powder, mulberry juice, moltital powder, moltital syrup, coconut oil andinulin were selected to use as ingredients. Crispy rice coated with healthy riceberry solution formula presented higher antioxidant activity (% inbihition) than that of normal formula. Keywords: crispy rice; riceberry powder; riceberry bran solution; mulberry juice; inulin